Palestinian Media Elite Attitudes towards Recording Cinemas in Addressing the Internal Situations: A Field Study - عيّاش علاء الدين محمد (ALBAHITH ALALAMI, 2017)
The follower of the history of cinema in the world notes that cinema started recording one and these films are varied in their subjects, while the life of man was the material of these films to be in a creative artistic style. If the Palestinian films produced by Palestinian directors do not have an impact on the local, Arab and international levels, this is due to the weakness in several technical fields or with the intention to make them bad or negligence of those who produce these films. This research deals with the role played by Palestinian films in dealing with the internal situation from the point of view of the Palestinian media elite in terms of their exposure to films and the motives of this exposure and the expectations achieved. The results of the research indicates that all the issues dealt with in the Palestinian films are not adequately addressed and that they do not express the international situation as required from the point of view of the respondents.